2018
DOI: 10.1002/csr.1701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corporate social responsibility disclosure on firms' sales performance: A perspective of stakeholder engagement and theory

Abstract: Corporate social responsibility (CSR) is receiving a supreme interest, and several experts have revealed the outcomes of CSR disclosure (CSRD) toward organizational performance across the globe. Nevertheless, less attention has been paid to empirical contribution with respect to marketing and sales management, especially from developing nations. This study investigates the impact of CSRD practices, that is, internal (ICSRD) and external (ECSRD) to organizational sales performance (OSP). Data were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 48 publications
5
75
0
Order By: Relevance
“…The external benefits of CSR have been highlighted in many literary sources (Lee, Cin, & Lee, ; Zappalà, ). For instance, several empirical studies have shown that an indirect positive correlation exists between CSR and firm profitability (Waheed & Yang, ). Furthermore, instead of focusing on the traditional concept of a single stakeholder, companies are required to utilize a multistakeholder approach in the stakeholder theory (Cornell & Shapiro, ; Wang, Hsieh, & Sarkis, ).…”
Section: A Review Of the Key Conceptsmentioning
confidence: 99%
“…The external benefits of CSR have been highlighted in many literary sources (Lee, Cin, & Lee, ; Zappalà, ). For instance, several empirical studies have shown that an indirect positive correlation exists between CSR and firm profitability (Waheed & Yang, ). Furthermore, instead of focusing on the traditional concept of a single stakeholder, companies are required to utilize a multistakeholder approach in the stakeholder theory (Cornell & Shapiro, ; Wang, Hsieh, & Sarkis, ).…”
Section: A Review Of the Key Conceptsmentioning
confidence: 99%
“…From an international perspective, such theory addresses business and social issues by informing the strategic decision‐making of organizations (Clarkson, ; Harrison et al, ). Although much research has been conducted on CSR, researchers are still striving to reveal the influence of CSR practices; thus, more studies are needed to understand CSR activities in different contexts worldwide (Arrive & Feng, ; Waheed & Yang, ). Additionally, the stakeholder theory suggests conducting more research in an international context, since CSR is a noteworthy global phenomenon, especially in developing countries (Harrison et al, ; Jamali & Neville, ; Waheed & Yang, ).…”
Section: Conceptual Background and Research Frameworkmentioning
confidence: 99%
“…Although much research has been conducted on CSR, researchers are still striving to reveal the influence of CSR practices; thus, more studies are needed to understand CSR activities in different contexts worldwide (Arrive & Feng, ; Waheed & Yang, ). Additionally, the stakeholder theory suggests conducting more research in an international context, since CSR is a noteworthy global phenomenon, especially in developing countries (Harrison et al, ; Jamali & Neville, ; Waheed & Yang, ). It is a prominent theory that has been widely considered in CSR studies by distinct experts globally (Clarkson, ; Reverte, ; Roberts, ; Waheed & Yang, ).…”
Section: Conceptual Background and Research Frameworkmentioning
confidence: 99%
“…Experts have revealed the outcomes of CSR disclosure towards organizational performance across the globe, including the aspect of marketing and sales that indirectly contribute to the CFP. The comprehensive analysis carried out by Waheed and Yang () on 450 small and medium enterprises (SMEs) from Pakistan unveiled the significantly higher effect of external CSR disclosure than internal CSR disclosure on marketing and sales performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experts have revealed the outcomes of CSR disclosure towards organizational performance across the globe, including the aspect of marketing and sales that indirectly contribute to the CFP. The comprehensive analysis carried out by Waheed and Yang (2019) on 450 small and medium enterprises (SMEs) from Pakistan unveiled the significantly higher effect of external CSR disclosure than internal CSR disclosure on marketing and sales performance. Brogi and Lagasio (2019) Although many extant studies focus on the relation between CFP and CSR reporting, less attention has been given to the shifting role of financial performance in CSR reporting in a changing institutional environment.…”
Section: Corporate Sustainable Development and Cfpmentioning
confidence: 99%